Analysis of Legal Concepts Used in the Act on Planning and Spatial Development - Krupa, Barbara (Management and Administration Journal, 2019)
In spatial planning and real estate management, there is a lack of conceptual order and which, without the legislator’s involvement, cannot be arranged either through interpretation or jurisprudence. Therefore, work on the codification of the construction process should start with issues related to the unification of the nomenclature used in the land register (real estate cadastre) with the nomenclature from other legal acts. Today, we are dealing with an incomprehensible situation, when the law is the source of inability to conduct rational spatial management, because they are based on the principle of construction freedom, which only serves the private interests of investors and landowners, at the expense of the common interest and the cost of protecting property neighbouring public investments.